Mapping the Solute–Solvent Interactions for the Interpretation of the Three Types of Solvatochromism Exhibited by Phenolate-Based Dyes - Mera-Adasme, R; Dominguez-Caru, M (Elsevier B.V., 2022)
We report the correlation between the hydrogen-bond donor acidity SA, the hydrogen-bond acceptor basicity SB, the solvent polarizability SP, and solvent dipolarity SdP with the type of solvatochromism exhibited by phenolates dyes. We use Catalán s multiparametric regression analysis of three sets of dyes exhibiting negative, inverted, and positive solvatochromism. We show that these three types of behavior can be differentiated by the solute–solvent interaction these dyes established in solution. Negative solvatochromic dyes exhibit a more robust response to SA than SdP, whereas SP is an essential solvent property for positive and inverted solvatochromic dyes. Our results can be rationalized for the sake of the structural features required for a particular kind of solvatochromism to take place; this is illustrated with selected examples where the introduction of atoms with a + M mesomeric effect or the increase in annulation of the dyes, decrease the SA and SdP sensitivity and increase the SP sensitivity of the dyes, and ultimately control the solvatochromism exhibited from a negative to an inverted or from an inverted to positive behavior. © 2022 Elsevier B.V.